The heuristic potential of constructivism in the formation and development of postacademic science - Burakevich, Irina E. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
The purpose of the article is to explicate the heuristic potential of constructivism in the formation and development of postacademic science. The displacment in philosophical and methodological discourse in the analysis of the state and basic trends of contemporary science is problematized. The article reveals that constructivism can lay the foundation for philosophical and methodological understanding of new phenomena in the development of scientific knowledge. The heuristic of the constructivist research program is explicated, on the one hand, by the example of the formation of a new disciplinary ontology based on the synergetic paradigm, and on the other, in the development of substantive and methodological aspects of technoscience and converging technologies.
Keywords: constructivism; postacademic science; technoscience; converging technologies; synergetics